سر سید احمد خان کے تفسیری اصول اور ان کا اطلاق:تفسیر القرآن کا خصوصی مطالعہ (Al-Qamar, 2023)
Sir Sayyad Ahmad explores that commandment of Allah Almighty is never against human common-sense understanding. Hence, Sir Sayyad in his Tafsīr Al-Qurʻān follows following principles. God (Allah Almighty) is real and true, and the Holy Qurʻān is the authentic book of Allah Almighty. Everything described in Holy Qurʻān is based on reality and nobody can refuse authenticity of Holy Qurʻān. Sir Sayyad called work of nature as laws of nature and Word of God as Holy Qurʻān. He enforces that both work of nature (Nature's Laws) and Word of Nature (Holy Qurʻān) runs parallel and can't be different. Laws of nature and the Holy Qurʻān can never be against each other. Principle of universal truth is followed. Man has been created to worship God. We can say that Religion has been blessed to man. This highlights the importance of "Man's Wisdom”. Hence man has been named as best of all creatures (Ashraf al-Makhlūqāt). Sir Sayyad further explores that there is nothing in the Holy Qurʻān against principles of nature. Holy Qurʻān is complete and it is commandment of Allah Almighty full of reality and truth. However, interpretation of revelation (Wahī) is necessary for understanding. Sir Sayyad enriched his Tafsīr al-Qurʻān with requirements of modern thinking, theology and scientific facts. Hence, he describes his point of views to mold Tafsīr into scientific Tafsīr.
Keywords: Qurʻān; Hadīth; Sir Sayyad Ahmad Khān; Interpretation; Tafsīr al-Qurʻān; Domain of Reason; Rational preference